Dampak Kemampuan Manajerial dan Peluang Pertumbuhan terhadap Kinerja IPO - Sibarani, Elisabeth Fransiska (Coopetition : Jurnal Ilmiah Manajemen, 2025)
The purpose of this study is to analyze the impact of management capabilities, growth opportunities, and company age on the performance of Initial Public Offerings (IPOs) in manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2024. IPO performance is measured by examining the phenomena of underpricing and overpricing, which reflect the difference between the offering price of shares at the time of the IPO and the share price traded on the first day in the secondary market. This study employs a quantitative approach using multiple linear regression analysis to investigate the impact of independent variables on IPO performance. The study utilizes data from 10 manufacturing companies that conducted IPOs within the specified timeframe. The findings indicate that managerial competence and growth prospects have a substantial positive impact on IPO performance. Conversely, company age does not significantly influence IPO outcomes. These findings provide insights that factors such as high managerial competence and good growth prospects play a crucial role in determining IPO success, while company age is not a primary factor in evaluating IPO performance in the Indonesian market. This study significantly enhances understanding of the factors influencing IPO performance in the Indonesian capital market.